Acoustic analysis of esophageal speech in patients after total laryngectomy - Wszołek, Wiesław; Modrzejewski, Maciej; Przysiężny, Monika (Archives of Acoustics, 2007)
Laryngeal cancer is one of the most frequent types of malignant tumor in male patients and it is located at position 5 among all the malignant tumors. The primary method of laryngeal carcinoma treatment for the cases with advanced cancer stages is the surgical treatment. In such a treatment the most frequent version is the total extraction of the organ. An effective postoperative therapy leads to the extension of the patients life-time, but the price is a serious disability, considerably impairing the patients communication with other persons. Therefore there is a problem of creation of a substitute voice and speech for those patients. The creation mechanism of the esophageal speech is the formation of vibration generator in the upper part of oesophagus. The substitute air container is formed by the oesophagus itself and the air vibrations in the upper part of oesophagus, generated during the anti-peristaltic motion of the air removed from oesophagus, create the primary pitch. The modulation of the fundamental pitch is obtained by the unchanged articulation organs and resonance cavities of the body. In the present paper an acoustic study of esophageal speech is described. An attempt has been made to determine the acoustic signal parameters, which can be useful in evaluation of esophageal speech quality.